Making Systems Safer Proceedings of the Eighteenth Safety-Critical Systems Symposium, Bristol, UK, 9-11th February 2010 - Dale, Chris; Anderson, Tom (Springer London : Imprint: Springer, 2010)
Making Systems Safer contains the papers presented at the eighteenth annual Safety-critical Systems Symposium, held at Bristol, UK, in February 2010. The Symposium is for engineers, managers and academics in the field of system safety, across all industry sectors, so the papers making up this volume offer a wide-ranging coverage of current safety topics, and a blend of academic research and industrial experience. They include both recent developments in the field and discussion of open issues that will shape future progress. The first paper reflects a tutorial - on Formalization in Safety Cases - held on the first day of the Symposium. The subsequent 14 papers are presented under the headings of the Symposium's sessions: Perspectives on Systems Safety, Managing Safety-Related Projects, Transport Safety, Safety Standards, Safety Competencies and Safety Methods. The book will be of interest to both academics and practitioners working in the safety-critical systems arena.